A Development Model of Pesantren Education in Muhammadiyah Boarding Schools: The Epistemological Perspective of Muhammad Abid Al Jabiri - Agus firmansyah; Yumidiana Tya Nugraheni; Dede Permana (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
ENGLISH: A Model for the Development of Pesantren Education in Muhammadiyah Boarding Schools from the Epistemological Perspective of Muhammad Abid Al JabiriObjective: This study aims to develop a model of pesantren education at Muhammadiyah Boarding School (MBS) Yogyakarta based on Muhammad Abid Al-Jabiri's epistemological perspective. Methods: This study employed a qualitative case study design. Data were collected through interviews, observations, and analyzed using the interactive model of Miles, Huberman, and Saldaña. Results: The findings indicate that the educational model is predominantly grounded in bayani epistemology, as reflected in the institutional vision and mission, curriculum structure, instructional materials, and teacher profiles. Although the national curriculum has been institutionally integrated, it has not achieved epistemological integration, resulting in a continuing dichotomy between religious and general knowledge. Conclusion: The development of pesantren education at MBS Yogyakarta remains primarily oriented toward bayani epistemology. Contribution: This study proposes a conceptual model for developing pesantren education through the integration of bayani, burhani, and irfani epistemologies to promote a more integrative, adaptive, and contextually relevant model of Islamic education.INDONESIA: Model Pengembangan Pendidikan Pesantren di Muhammadiyah Boarding School: Perspektif Epistemologi Muhammad Abid Al-JabiriTujuan: Penelitian ini bertujuan mengembangkan model pendidikan pesantren di Muhammadiyah Boarding School (MBS) Yogyakarta berdasarkan perspektif epistemologi Muhammad Abid Al-Jabiri. Metode: Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui wawancara, observasi, kemudian dianalisis menggunakan model interaktif Miles, Huberman, dan Saldaña. Hasil: Model pendidikan MBS Yogyakarta didominasi oleh epistemologi bayani yang tercermin dalam visi dan misi, struktur kurikulum, materi pembelajaran, serta latar belakang pendidik. Integrasi kurikulum nasional telah dilakukan, tetapi belum mencapai integrasi epistemologis sehingga masih terjadi dikotomi antara ilmu agama dan ilmu umum. Kesimpulan: Pengembangan pendidikan pesantren di MBS Yogyakarta masih bertumpu pada epistemologi bayani sebagai landasan utama penyelenggaraan pendidikan. Kontribusi: Penelitian ini menawarkan model pengembangan pendidikan pesantren berbasis integrasi epistemologi bayani, burhani, dan irfani sebagai kerangka konseptual untuk memperkuat pengembangan pendidikan Islam yang lebih integratif, adaptif, dan kontekstual.